Analisis Perbandingan Penerapan Metode AHP-SAW dan AHP-TOPSES Dalam Pemilihan Mahasiswa Terbaik Prodi Ilmu Keperawatan - Muhamad Wahyu Tirta; Muhammad Khumaidi Nursyarif; Hamada Zein; Rita Yulfani; Melisa Nur Aini; Farhan Akbar (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2024)
Student graduation becomes a separate assessment reference in a higher education institution. Things that are taken into consideration are efforts to carry out assessments to determine the best students. The data used comes from the graduation achievements of students from the Nursing Profession Study Program, Faculty of Nursing, Muhammadiyah University, East Kalimantan, which consists of four criteria. Based on these problems, the author conducted research aimed at analyzing the use of Decision Support System methods. The method used in this research uses a combination of AHP-SAW and AHP-TOPSIS. The results obtained explain that both methods obtain ranking results in the same order even though the Priority value of each method is different. Where rank 1 for each method is A1 with an AHP-SAW Priority Value of 100 and AHP-TOPSES of 1, likewise in the next ranking order.